ANALISA PENILAIAN KINERJA KARYAWAN DENGAN METODE FUZZY SIMPLE ADDITIVE WEIGHTING Pada PT. Unilever Indonesia Tbk Skin Deo Factory SBU Production Tube - Elik Yuli Ariato; Fernando B Siahaan (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Abstract - ssessment of employee performance is critical to future evaluation and planning of the company. Employee performance appraisal is absolutely done to know the achievement that will be achieved by every employee. Whether the achievement is good, enough or less. The purpose of this study is to assist companies in determining the assessment of employees who are objective. In the discussion, there are differences in the ranking done manually and the FSAW method with three variables are work quality, work skills and attendance. Conclusion with Fuzzy simple Additive Weighting (FSAW) method can produce accurate and fast information to satisfy employees to improve their performance.Keywords: Employee, FSAW, Employee Performance